Tingkat Kerusakan Jaringan Darah Ikan Mas (Cyprinus carpio) yang Dipaparkan pada Media Zn-Sulfat (ZnSO4) - Siti Khotimah, Ade Syahrial, Tri Rima Setyawati, (Jurnal Protobiont, 2013)
Industrial activities should produce waste and if it is discharge into waters continually can be resulted in changes to water quality. One of the wastes generated from industrial activities that affect the quality of the aquatic environment is Zinc (Zn). The purpose of this study was to investigate the effect of Zinc (Zn) on the number of erythrocytes, leucocytes, hemoglobin levels and erythrocyte morphological damage in goldfish (Cyprinus carpio). Impact test was carried out by using 54 goldfishes Cyprinus carpio. It was accomplished in 3 different groups of treatment and repeated 3 times. Then, a blood sample from each treatment group of goldfish was taken. The result showed that the number of erythrocytes decreased by 69.2%. The number of erythrocytes after exposure was 0.5 x 106 cells/mm3. While the amount of leucocytes increased by 63.59%. The number of leucocytes was 0.235 x 106 cells/mm3. Hemoglobin levels were unchanged. Zinc (Zn) accumulation in blood achieved its highest level of 1.96 mg/l with the accumulation rate of 196%. The erythrocytes morphological damage was spherocytes (18.44%) and seroid (80.5%). It occurred at a concentration of ZnSO4 1 ppm with exposure for 6 weeks.